(untitled) (The Educator Journal, 2024)
The main purpose of this research was to improve geometry through constructivist teaching and learning and to explore the students’ experiences in learning using GeoGebra-designed modules. The design of this study was a teaching experiment using a qualitative research method. Data was collected through interviews, written text, participant observation, field notes, reflection notes, and field photography. Ninth grade students at a private school in Pokhara were the research participants. The data was coded into different meaningful themes. The result shows that use of GeoGebra models on triangle and parallel lines properties would be helpful not only in the development of teachers ‘efficiency in the process of teaching but also help students’ learning cultures through visualization, demonstration, construction, and verification fostering a deeper sense of observation with proper reasoning. Overall, students showed positive and better learning experiences towards learning geometry lines, angles and triangles properties verification with conceptualization through GeoGebra design models. The findings of this study on incorporating GeoGebra developed models into geometry instruction will be beneficial to students, readers, trainers, researchers, and educators to learn and teach geometry more successfully with enthusiasm.